APLIKASI PENCARIAN DAN PENGUMUMAN BARANG HILANG “CARLIK-CARI PEMILIK” BERBASIS MOBILE - Joko Dwi Mulyanto; ragil wijianto; Saefudin Saefudin; Affan Sholahuddin (Informatics and Computer Engineering Journal, 2023)
Generally, every soul has almost experienced the loss of something that previously existed and had no longer exists. The event off loss, especially of property, can cause anxiety for someone who is looking for lost items. This is because there is a possibility of someone will find the lost items. Currently, the process of searching and announcing lost items is not going well because of existing factors such as that information does no spread widely. Therefore, a media is needed that can be a place to accommodate information on the search and find of lost items with the intention of helping people find and return lost items. Android-based application development using Dart programming language, Flutter framework, Firebase database, and Nominatim API. Application development method using Software Development Life Cycle (SDLC) method with waterfall model and tested with black box testing method. The results of the application development indicate the application can run well according the required specifications and can be seen from black box testing with valid results